2017
DOI: 10.4172/pharmaceutical-sciences.1000217
|View full text |Cite
|
Sign up to set email alerts
|

HPLC and HPTLC methods for Simultaneous Estimation of Quercetin and Curcumin in Polyherbal Formulation

Abstract: Baghel, et al.: Chromatographic Analysis of Quercetin and CurcuminFast, sensitive, precise and selective high performance liquid chromatography and high performance thin layer chromatography methods were developed for the simultaneous estimation of curcumin and quercetin in a polyherbal formulation. Validation of these methods were carried out with respect to linearity, range, precision, accuracy and robustness. Both methods were applied to a polyherbal formulation to find the amount of curcumin and quercetin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The assay was performed on 4.08 mM PEI solutions in 150 mM NaCl at various pH. Secondary amines react with ninhydrin in acidic medium to give iminium salt [ 30 ]. The iminium salt has a characteristic yellow color with optimum UV-Vis absorbance at 440 nm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assay was performed on 4.08 mM PEI solutions in 150 mM NaCl at various pH. Secondary amines react with ninhydrin in acidic medium to give iminium salt [ 30 ]. The iminium salt has a characteristic yellow color with optimum UV-Vis absorbance at 440 nm.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of the iminium salt requires both a transferable electron pair on the amine nitrogen and an acidic medium. The reaction between ninhydrin and a secondary amine to form the iminium salt proceeds in two stages: (1) the lone-pair of electrons from the nitrogen of PEI’s secondary amine is transferred to the ninhydrin complex; and (2) the ninhydrin complex undergoes hydrolysis in the acidic medium to form iminum salt [ 30 ]. Acidic pH decreases iminium salt formation in linear PEI (i.e., absorbance decreases in the ‘weak acidic’ region, Fig 6D ), which can be attributed to the decrease in the number of nitrogen atoms being able to donate lone-pair of electrons as they become protonated.…”
Section: Resultsmentioning
confidence: 99%
“…Recent discoveries in the field of Morus alba L. phytochemicals revealed that Morus alba L. twig extracts contain polyphenols, which are major effective antioxidants. [26][27][28][29] Meanwhile, monomer polyphenols including oxyresveratrol, resveratrol [30,31] , mulberroside, rutin [32] , quercetin [33] , and morin, [34] which exist in Morus alba L. twig are more extensive, have high antioxidant activity, and are effective scavengers of free radicals. Six polyphenols, in particular, including rutin, quercetin, and morin, have been isolated and shown to possess high free radical scavenging activity [35] , and resveratrol and rutin can protect against DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, numerous methods, including UV spectroscopy [16,17], RP-HPLC [18][19][20], HPTLC [21,22] and others, are available for determining RIF both alone and in conjunction with various drugs in a variety of dose forms. A few methods, including HPLC [23][24][25][26], UV spectroscopy [27] and HPTLC [28][29][30][31], have been taken into consideration for the assessment of QUE both alone and in conjunction with different drugs in different forms of dosage. The previously mentioned chromatographic strategies are broadly utilized and suggested; however, these techniques require mind-boggling and costly instrumentation, arrangement for use and removal of solvents, work escalated test planning methodology and individual aptitudes [32,33].…”
Section: Introductionmentioning
confidence: 99%